Emerging drug combinations to optimize renovascular protection and blood pressure goals - Escobar, Carlos (Dove Medical Press, 2012)
Hypertension and renal disease are closely related. In fact, there is an inverse linear relationship between renal function and prevalence of hypertension. Hypertensive patients with renal dysfunction exhibit a poor clinical profile, which markedly increases their risk for cardiovascular outcomes. This review considers the available evidence on the best therapeutic approach for optimizing renovascular protection in the hypertensive population. To effectively reduce or at least slow the establishment and progression of renal disease in the hypertensive population it is critical to reach blood pressure targets. Many studies have shown that angiotensin-converting enzyme inhibitors and angiotensin receptor blockers prevent or at least delay the development of microalbuminuria in patients with hypertension and type 2 diabetes, reduce the incidence of overt diabetic nephropathy, and are also beneficial in patients with nondiabetic renal disease. Therefore, renin-angiotensin system (RAS) inhibition plays a key role in the prevention of renal outcomes. As the majority of patients with hypertension will need at least two antihypertensive agents to achieve blood pressure goals, the use of RAS inhibitors is a mandatory part of antihypertensive therapy. The question of which antihypertensive agent is the best choice for combining with RAS blockers should be considered. Many studies have shown that diuretics and calcium channel blockers are the best choice. However, more studies are needed to clarify the subgroups of patients who will benefit more from a combination with a diuretic or from a combination with a calcium channel blocker. To date, RAS inhibitors recommended in this context are angiotensin-converting enzyme inhibitors and angiotensin receptor blockers. Aliskiren, the first oral direct renin inhibitor available, has shown promising results.